The Management of Death Charity Financial Fund: A Study of Principles and it's Application in Ar-Rahmah Sungai Buaya Mosque, Rawang, Selangor Malaysia - Setiyawan Gunardi; Nurul Thaqifah Mat Arop; Zawin Hannan Sofea Shahbuddin; Azman Ab. Rahman; Khairunneezam Mohd Noor; Ahmad Zaki Salleh; Syed Mohd Najib Syed Omar (International Journal of Professional Business Review (JPB Review), 2024)
Non-Indexed Publication